Metabolic Imaging of Deep Brain Stimulation in Meige Syndrome - Liu, Jiayu; Li, Lei; Li, Yuan; Wang, Qian; Liu, Ruen; Ding, Hu (Frontiers in Aging Neuroscience, 2022)
Objectives The subthalamic nucleus (STN) has been shown to be a safe and effective deep brain stimulation (DBS) surgical target for the treatment of Meige syndrome. The aim of this study was to compare changes in brain metabolism before and 6 months after STN-DBS surgery. Methods Twenty-five patients with primary Meige syndrome underwent motor function assessment, including the Burke–Fahn–Marsden Dystonia Rating Scale movement (BFMDRS-M) and disability subscale (BFMDRS-D) and positron emission tomography with an 18[F]-fluorodeoxyglucose scan before and 6 months after STN-DBS surgery. For the voxelwise metabolic change assessment, the p-value was controlled for multiple comparisons using the familywise error rate. Results There was a significant decrease in BFMDRS-M scores 6 months after STN-DBS, from 10.02 ± 3.99 to 4.00 ± 2.69 (p < 0.001). The BFMDRS-D scores also decreased significantly from 4.52 ± 2.90 to 0.64 ± 1.29 (p < 0.001). In the left hemisphere, hypermetabolism was found in the occipital lobe, superior parietal gyrus, postcentral gyrus and thalamus. In the right hemisphere, hypermetabolism was found in the lentiform nucleus, precuneus and precentral gyrus in patients with Meige syndrome receiving DBS. In addition, the bilateral inferior temporal gyrus and middle frontal gyrus exhibited glucose hypermetabolism. Conclusion Our findings indicate that STN-DBS has a significant effect on metabolic level in the brain, which may be an important mechanism for the treatment of Meige syndrome using STN-DBS.